1987
DOI: 10.1111/j.2042-7158.1987.tb06986.x
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic activities of octopamine and synephrine stereoisomers on guinea-pig atria and trachea

Abstract: The activities of the (-)- and (+)-forms of m- and p-octopamine and m- and p-synephrine on beta 1- and beta 2-adrenoceptors in guinea-pig atria and trachea have been compared with that of noradrenaline. The rank order of potency of the (-)-forms on beta 1-adrenoceptors was noradrenaline greater than m-synephrine greater than m-octopamine = p-octopamine greater than p-synephrine. m-Synephrine was 100-fold, m- and p-octopamine about 6000-fold, and p-synephrine about 40,000-fold less active than noradrenaline. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 8 publications
4
42
0
Order By: Relevance
“…Since the concentration of NA is approximately 100 times greater than either moctopamine or p-octopamine in most sympathetically innervated organs, it is apparent that if stimulation of adrenergic nerves leads to the co-release of these three amines in amounts proportional to their concentration, it is unlikely that modulation of NA neurotransmission by m-or p-octopamine can be mediated by a,-or X2-adrenoceptors. Both m-and p-octopamine are less active than (-)-NA by more than 3 orders of magnitude on P,-adrenoceptors, and by more than 4 orders of magnitude on P2-adrenoceptors (Jordan et al, 1987). It is concluded that, if m-and p-octopamine have a physiological function, then this function is not mediated by any of the four adrenoceptor subtypes.…”
Section: Discussionmentioning
confidence: 87%
“…Since the concentration of NA is approximately 100 times greater than either moctopamine or p-octopamine in most sympathetically innervated organs, it is apparent that if stimulation of adrenergic nerves leads to the co-release of these three amines in amounts proportional to their concentration, it is unlikely that modulation of NA neurotransmission by m-or p-octopamine can be mediated by a,-or X2-adrenoceptors. Both m-and p-octopamine are less active than (-)-NA by more than 3 orders of magnitude on P,-adrenoceptors, and by more than 4 orders of magnitude on P2-adrenoceptors (Jordan et al, 1987). It is concluded that, if m-and p-octopamine have a physiological function, then this function is not mediated by any of the four adrenoceptor subtypes.…”
Section: Discussionmentioning
confidence: 87%
“…Two of four active foodstuffs are fruit parts of Citrus species. It has been reported that citrus species are rich sources for various bioactive compounds such as flavonoids, adrenergic amines, limonoids, and coumarines [14,15], and synephrine alkaloids, known to be adrenergic agonists [16,17], are useful for the treatment of overweight and obesity by facilitating adipolysis [18]. Therefore, it seems to be natural that Citrus species exerted adipolytic effect in vitro.…”
Section: Resultsmentioning
confidence: 98%
“…41) The cardiovascular effects of m-synephrine and p-synephrine were clearly distinct as a result of their markedly different adrenergic receptor binding activities, with m-synephrine exerting markedly greater binding to various α-receptor subtypes as well as β-1 and β-2 receptors. 9,[42][43][44] The well documented cardiovascular effects of m-synephrine cannot therefore be extrapolated to p-synephrine and bitter orange extract. So Stohs et al indicated that receptor binding studies involving tissues indicate that exhibits poor binding affinities or non-specificities for α-adrenoreceptor subtypes as well as β-1 and β-2 adrenoreceptors.…”
Section: Discussionmentioning
confidence: 99%